ARABIC LANGUAGE MANAGEMENT INTENSIVE PROGRAM IN RELIGIOUS SPECIALIZATION AT MAN 2 MALANG CITY - Zamroni, M. Rozy; Fajrin, A'yunin Aditya; Zahroh, Tabassum Aliyatuz; Kholid, Nur (Idaarah: Jurnal Manajemen Pendidikan, 2023)
The purpose of this research is to determine the planning and actuating of management in the intensive Arabic program for religion specialization as the MAN-PK stub of MAN 2 Kota Malang and to analyze the supporting factors and obstacles found in the process while running the program. The method used in this research is a qualitative method. The data obtained by observation and interviews were then analyzed descriptively. The results of this study are; (1) planning management program is carried out properly in accordance with the objectives of the program; (2) supporting teachers used strategies that accordance with planning and objectives in implementing the program; (3) the majority of students have the same orientation even though some students think to change their specialization is one of the obstacles in this intensive Arabic language program.